2018
DOI: 10.21873/invivo.11303
|View full text |Cite
|
Sign up to set email alerts
|

Partial Protection of Paclitaxel-induced Neurotoxicity by Antioxidants

Abstract: Abstract. Background Paclitaxel is an anticancer drug that inhibits calcium-induced depolymerization of tubulin and thus blocks the progression of mitosis (1). It is clinically applied for the treatment of ovarian, breast, stomach and non-small cell lung cancer (2, 3). When used clinically, it causes severe side-effects such as leucopenia. thrombocytopenia, neutropenia and fatigue (4) and anorexia and constipation (5). Patients who received platinum treatment with a taxane were more likely to experience grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…We have previously reported that cisplatin showed potent cytotoxicity against differentiated PC12 cells [ 34 ], while taxanes (paclitaxel, docetaxel) and amyloid peptides (Aβ 1–42 , Aβ 25–35 ) showed cytostatic effects [ 34 , 35 ]. A cell sorter analysis demonstrated that cisplatin induced the apoptosis, characterized by the accumulation of the subG 1 population ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that cisplatin showed potent cytotoxicity against differentiated PC12 cells [ 34 ], while taxanes (paclitaxel, docetaxel) and amyloid peptides (Aβ 1–42 , Aβ 25–35 ) showed cytostatic effects [ 34 , 35 ]. A cell sorter analysis demonstrated that cisplatin induced the apoptosis, characterized by the accumulation of the subG 1 population ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the SI (=CC 50 /EC 50 ) value of polyphenols, plant extracts and antioxidants, calculated using the data from our original papers [ 33 , 35 , 38 , 39 ] and the present study ( Table 2 ). The higher the SI value, the stronger the neuroprotective activity would be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium was completely removed by suction and replaced with 0.1 ml of differentiation medium (serum-free DMEM containing 50 ng/ml NGF). Cells were then incubated for 3 days to induce neuronal differentiation characterized by neurite formation (referred to as day 3 cells) ( Figure 1) (20). To induce more mature cells, cells were inoculated at 2×10 3 cells per microwell.…”
mentioning
confidence: 99%
“…Differentiated cells were defined as the cells in which the extended neurites exceeded the longest diameter of each cell, assessed under a light microscope [EVOSfl; ThermoFisher Scientific, Waltham, MA, USA; described in Figure 1A of (21) After incubation for 48 h, the viable cell number was determined by MTT method. MTT concentration was reduced from 0.2 mg/ml to 0.1 mg/ml, due to its cytotoxicity towards neuronal cells (20). The cells were incubated for 1 h, and the formazan precipitate was dissolved in DMSO and the absorbance at 560 nm was measured (which reflects the relative viable cell number, more precisely cellular mitochondrial activity) with a plate leader (Infinite F 50 R;TECAN, Kawasaki, Japan).…”
mentioning
confidence: 99%